[PP.38.04] NET BLOOD PRESSURE REDUCTION FOLLOWING 9-MONTH OF LIFESTYLE AND HIGH-INTENSITY INTERVAL TRAINING INTERVENTION IN INDIVIDUALS WITH ABDOMINAL OBESITY. (September 2016) - Sosner, P.; Bosquet, L.; Herpin, D.; Guilbeault, V.; Latour, E.; Paquette-Tannir, L.; Juneau, M.; Nigam, A.; Gayda, M.
Abstract : Objective: We aimed to study the impact of a combined long-term lifestyle and high-intensity interval training (HIIT) intervention on blood pressure (BP) in individuals with abdominal obesity, taking into account the regression-to-the-mean (RTM) phenomena (net-change). Design and method: One hundred fifteen participants (age: 53 ± 9 years; 84 women; waist circumference (WC): 111 ± 13 cm; systolic/diastolic BP (SBP/DBP): 133 ± 13 / 82 ± 8 mmHg; 13% diabetics, 12% smokers, 30% under antihypertensive therapy) were retrospectively analyzed before and after a combined lifestyle (Mediterranean diet nutritional counselling) and HIIT program twice a week. Anthropometric measurements and resting BP were assessed at baseline and after 9 months of program. Results: After 9 months, we observed an improvement in weight (−5.2 ± 5.6 kg), BMI (−1.87 ± 1.98 kg/m2), WC (−6.3 ± 6.0 cm) and an average SBP/DBP net-decrease of −5.1 ± 13.7 / −2.8 ± 8.7 mmHg (Table 1). These changes were not uniform: 67 participants (58%) decreased their SBP by 2 mmHg or more, reaching −8.7 ± 12.3 / −4.1 ± 8.0 mmHg (SBP/DBP). The characteristics of responders were a higher baseline BP than non-responders (SBP/DBP: 137.2 ± 13.7 / 83.1 ± 7.3 vs. 127.0 ± 10.3 / 80.0 ± 7.3 mmHg, P < 0.05) and a higher proportion of participants with a baseline BP > = 130/85 mmHg (81% vs. 52%, P = 0.001) or with a metabolic syndrome (75% vs. 54%, P = 0.02). Figure. No caption available. Conclusions: A combined long-term lifestyle and HIIT intervention has a beneficial effect on net-BP-change in patients with abdominal obesity and a baseline BP > = 130/85 mmHg.